The Change Which Remains the Same: Towards a Decolonisation Which Does Not Recolonise - Steven Friedman (University of Johannesburg, 2021)
In his celebrated study of colonisation, The Intimate Enemy, Ashis Nandy observes of Indian responses to British colonisation: ‘The pressure to be the obverse of the West distorts the traditional priorities in the Indian’s total view of the…universe…It in fact binds him (sic) even more irrevocably to the West.’ This problem stems, he adds, from a tendency by both coloniser and anti-colonial thinker to ‘absolutise the relative difference between cultures’. This article will argue that Nandy’s observation is an essential element in a South African response to colonisation which does not repeat colonialism’s assumptions in the name of replacing them. In particular, it argues against an essentialism in which a reified ‘Western culture’ is replaced by an equally reified ‘African culture’ which is just as constraining and just as likely to be used as a rationale for domination as the colonial ideology it purports to reject. It will further argue that we avoid the trap of which Nandy warns if we define intellectual colonisation as an ideology which seeks to suppress or eliminate modes of thought which do not conform to a dominant set of values and its antidote, decolonisation, as the removal of this constraint, not as its replacement by new constraints. This decolonisation does not seek to abolish ‘Western culture’ but to integrate it into a world view in which it takes its place alongside African, Asian, and Latin American cultures. It therefore recognises the syncretic nature of all cultures and views of the world and seeks to enhance, rather than obstruct, conversations between them.